Chapter 9 Who is Europe? Staging the making of Europe in creative documentary film - McDonald, Ian (Taylor & Francis, 2019)
This chapter is a set of accounts of the film Who is Europe? It is a conversation between the filmmaker and the editors of this book, some of whom were directly involved in the filmmaking too. It is a good idea to watch the film before reading on. It is available at https://vimeo.com/303706985.